Is pneumatosis cystoides intestinalis a lymphatic pathology?: A case of small bowel lymphangioma and subsequent development of pneumatosis cystoides intestinalis in a 57-year-old female. Issue 1 (24th January 2019) - Harris, Emily; Giannotti, Giovanni
Abstract: The etiology of pneumatosis cystoides intestinalis (PCI) is multifactorial and its corresponding treatment is similarly complex. One causation of PCI, is lymphatic disruption. This association is discussed in this case report involving an incident of abdominal lymphangioma and subsequent development of PCI in a 57-year-old female. The purpose of this paper is to further understand the pathology of PCI, specifically as it relates to lymphatic disruption. Furthermore, the purpose of this article is to define a treatment protocol for this disease when it involves lymphatic pathology; i.e. when a surgical vs conservative approach is warranted.